Clinical presentation and metabolic consequences in 40 breastfed infants with nutritional vitamin B12 deficiency--what have we learned? - Honzik, Tomas; Adamovicova, Miriam; Smolka, Vratislav; Magner, Martin; Hruba, Eva; Zeman, Jiri (European journal of paediatric neurology, 2010)
BACKGROUND: Maternal vitamin B(12) (Cbl) deficiency causes nutritional Cbl deficiency in breastfed infants. AIMS: To analyse clinical presentation and metabolic consequences in 40 breastfed infants with Cbl deficiency. METHODS: Cbl levels in serum and breast milk were determined by an electrochemiluminescence immunoassay, methylmalonic acid level by GC/MS, plasma homocysteine by HPLC and propionylcarnitine by MS/MS. Profound Cbl deficiency was found in 17 children (69 ± 17 ng/l, controls 200-900), and milder Cbl deficiency in 23 children (167 ± 40 ng/l). Maternal Cbl deficiency was mostly caused by insufficient Cbl absorption. Only six mothers were vegetarian. RESULTS: The average age at diagnosis was 4.4 ± 2.5 months. Clinical symptoms included failure to thrive (48% of children), hypotonia (40%), developmental delay (38%) and microcephaly (23%). 63% of children had anaemia (megaloblastic in 28% of all children). All but one patient had methylmalonic aciduria, 80% of patients had hyperhomocysteinemia and 87% had increased aminotransferases. Propionylcarnitine was elevated in two out of 25 infants. Comparing groups with severe and mild Cbl deficiency, a marked difference was found in severity of clinical and laboratory changes. CONCLUSION: Maternal Cbl status and diagnostic delay are the major factors influencing severity and progression of Cbl deficiency in breastfed infants. In our cohort, propionylcarnitine was not sufficiently sensitive marker of Cbl deficiency. Although symptoms are reversible on Cbl substitution, permanent neurological damage can result. Selective screening for Cbl deficiency is indicated in all breastfed infants with failure to thrive, hypotonia, developmental delay, microcephaly or megaloblastic anaemia. The best prevention in future could be the screening of all pregnant women.
Keywords: Nutritional Physiological Phenomena; Retrospective Studies; Vitamin B 12 Deficiency; kojenec; vitamin B 12; mužské pohlaví; Infant; Breast Feeding; Child, Preschool; ženské pohlaví; retrospektivní studie; předškolní dítě; Humans; Vitamin B 12; kojení; fyziologie výživy; Female; nedostatek vitaminu B12; lidé; Male